2021
DOI: 10.1155/2021/8094640
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Characteristics of Carbon Nanotubes‐Reinforced Plasma‐Sprayed Al2O3‐TiO2 Ceramic Coatings

Abstract: Thermal-sprayed coatings are widely used in various oil and gas industries for wear and corrosion applications. However, increasing performance and requirements make conventional coatings inadequate for future needs. Furthermore, the heat conductivity of bulk materials cannot be minimized easily. Therefore, the use of low porous coating with nanocomposite doping is an effective way to produce coatings with reduced thermal conductivity. Plasma-sprayed Al2O3-TiO2 coatings are found in a wide range of application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is not necessary to stress the significance of clean air in maintaining a decent and healthy lifestyle. As a result, emissions must be significantly reduced in order to preserve a relatively secure planet for future generations [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is not necessary to stress the significance of clean air in maintaining a decent and healthy lifestyle. As a result, emissions must be significantly reduced in order to preserve a relatively secure planet for future generations [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For its greater surface potential, the sharp-edged plate-shaped silicon phase in the aluminum alloy was thermodynamically unstable. In comparison to a central section of the silicon plates, maximum stress is likely higher at these sharp corners [24].…”
Section: Relation Exists Between Mechanical Property Andmentioning
confidence: 98%
“…The study also found that the friction and wear properties of chemically bonded ceramic coatings under different curing agents are related to the ratio of AlPO 4 :Al 2 O 3 . Chaitanya et al [18] prepared and characterized the wear-resistant and low porous coatings of Al 2 O 3 + 3 wt-% TiO 2 and respective carbon nanotube (CNT) doped coatings. They found that the formation of cracks as well as micropores is decreased by the addition of carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%